Childhood maltreatment and adult's provisions of emotional support given to family, friends, and romantic partners: An examination of gender differences. (August 2020) - Fitzgerald, Michael; Hamstra, Cailyn; Ledermann, Thomas
Abstract: Background: Research has established that childhood maltreatment is associated with interpersonal problems across the life course. Less is known regarding how maltreatment is linked with adult's provision of emotional support to their family members, friends, and romantic partners. Objective: To examine how maltreatment severity is associated with adult's provisions of emotional support to family members, friends, and romantic partners and examine differences between men and women. Participants and setting: A sample of 1255 adults (56 % women) was collected between 2005 and 2009. Methods: Data are from the National Survey of Midlife Development in the United States (MIDUS). Participants completed retrospective survey reports of childhood maltreatment and current provision of emotional support provided to family members, friends, and romantic partners. Results: Using hierarchical regression analysis, childhood maltreatment was negatively associated with provisions of emotional support provided to family members ( b = -0.013, p < .05), friends ( b = -0.013, p < .05), and romantic partners ( b = -0.016, p < .05) above and beyond other childhood adversities, current mental health symptomology, and current stress. Gender moderated the relationship for friends ( b = 0.012, p < . 05) and romantic partners ( b = 0.015, p < .05) where women provided more emotional support than men while no gender differences in support provided to family members ( b = 0.009, p > .05.) Conclusion: Childhood maltreatment contributes to less provision of emotional support to family members, friends, and spouses for both men and women and is particularly detrimental for men. Clinical Implications are discussed.